Intervenção psicológica com mandalas: técnica do desenho de mandala em um grupo de crianças de 8 a 12 anos, vítimas de abandono, moradoras em casa de abrigo - Dibo, Monalisa (2011)
The mandala, as a religious symbol, has the objective of enhancing the encounter of the conscience with the Self, through a religious posture. This paper uses a religious instrument to benefit the mental health of some children. The goal of this thesis is to study the effects of mandala drawings in children between the ages of 8 and 12, victimized by abandonment, living in shelters. The effects studied here refer to stress, anxiety and worrying, depressive moods, interest in social and school activities and cognitive and physical fatigue. It is a qualitative as well as quantitative research that highlights the meanings and the processes measured both in terms of quantity and frequency. The tools utilized were: the CAD Clinical Assessment of Depression; Child Stress Symptoms Inventory (Escala Stress Infantil), questionnaires for the technical staff; printed religious mandalas; printed coloring drawings; and printed drawings of a circle. The sample included 34 children, 12 males and 22 females. All children were sheltered at Associação dos Amigos do Menor pelo Esporte Maior (AMEM) in São Paulo at the time of the research. These children were enrolled in the elementary school from 2nd to 6ª grade, corresponding to the third and seventh grade in 2009. The children were divided into two groups: a control group (doing coloring of printed drawings) and experimental group (doing mandala painting). Each group comprised 17 children. The data obtained confirmed the hypothesis, i.e. the mandala drawings induced changes in the children s behavior, promoting meaningful improvements regarding children stress, depression, anxiety and worrying, in their school and social interests as well as in their cognitive and physical behavior. Hence, we could say that the mandala drawing technique was an enriching and efficient activity for the psychic life of these children. It allowed access to the creative ludic world of the children, encouraged a way of self-discovery and enlivenment of their creative ability, enabled a more balanced relationship between self and ego, generated serenity and well-being, lessened stress and depression, which resulted in moments of emotional transformation, inner contact, order, stabilization and harmony, therefore allowing better integration. This thesis demonstrates that a religious tool, developed by millennial cultures, aiming the connection of the individual with their center and with God, can be applied to a group of children, generating that connection. This confirmation could be observed from the tests and as narrated by the children